Physical Condition Profile of Jombang Karate Club (JKC) Athletes in 2023 - Aditya Harja Nenggar; Yully Wahyu Sulistyo (Universitas Majalengka, 2023)
This study aims to determine the physical condition profile of karate athletes at Jombang Karate Klub (JKC). This research is descriptive-quantitative; the sampling technique used is purposive sampling; the sample in this study consisted of 15 athletes, consisting of 8 female athletes and 7 male athletes. Instruments in this study include tests of flexibility with the Sit and Reach test, strength with the Push Up test, speed with the sprint test, agility with the running back and forth test, explosive power with the standing board jump test, and endurance with the Multistage Fitness Test. Data analysis techniques using descriptive analysis. Based on data calculations, it is known that 40% (6 athletes) have very good physical conditions, 26.5% (4 athletes) are in the good category, 20% (3 athletes) are in the sufficient category, and as many as 13.4% (2 athletes) are in the less category, and 0% (0 athletes) are in the very less category. The physical condition of karate athletes is in the very good category. It is necessary to have regular physical condition tests for athletes so that the development of the athlete's physical condition can be known. Further research is expected to use a wider population, so that the data is more extensive, and this research is expected to be used as a reference for further research.